Testing the performance of NoSQL databases via the Database Benchmark tool - Krstić, Lazar J.; Krstić, Marija S. (Vojnotehnički glasnik / Military Technical Courier, 2018)
NoSQL is often used as a successful alternative to relational databases, especially when it is necessary to provide adequate system dimensioning, usage of a variety of data types and high efficiency at a low cost for maintaining consistency. The work is conceived in a manner that covers the general concept of a database, i.e. the concept of relational and non-relational databases, which are substantiated by all important aspects and in an appropriate context. After analyzing the types of NoSQL databases, emphasis is placed on explaining their advantages and disadvantages, as well as on an overview of the NoSQL and SQL database comparison. The final part of the paper presents the results of testing the performance of NoSQL databases, obtained though the Database Benchmark tool. The aim of the paper is to highlight all the details of NoSQL databases in order to establish the justification of their application in practice.
Keywords: Performance testing; NoSQL databases; Relational databases; Databases